Muslim Women in Past and Present Governmental Leadership: Case of Rulers of the Sultanate of Aceh and the Fifth President of the Republic of Indonesia - Ita Syamtasiyah Ahyat (Journal of Education and Learning (EduLearn), 2014)
A Muslim woman is a woman who believes in Islam.  In its historical path, Indonesia has been led by Muslim women along with the development of Islam in the Archipelago in the 17th century. A case example among others is the Sultanate of Aceh during the colonial period. During the independence period, Indonesia was also led by a Muslim woman as the fifth President of the Republic of Indonesia around the early 21st century. In these case examples of Muslim women as rulers, they received criticism during their reigns from men who viewed the matter from the perspective of Islam. This made an impact on the ongoing governance and the people.  The article discusses how Muslim women leaders faced these criticisms from men who viewed the matter from the point of view of Islam and how it affected their governmental administration. Therefore, the article is expected to be able to reconstruct how Muslim women leaders face criticism from men who viewed the matter from the perspective of Islam. Research in this paper is conducted through historical method actions, preceded by source collection, selection and interpretation along with the reconstruction of the intended events, which is referred to as historiography. The study is also based on local sources, documents, and writings of related critics on the issue.